Implementation of Fast Track Method in Bore Pile Foundation Construction for Regional General Hospital Development Projects - Doni Setiawan; Lily Kholida; Prihadmadi Anggoro Seno (Universitas Negeri Padang, 2025)
In a project, running work will require a good planning, scheduling and control, and are influenced by factors such as good resources, material availability, equipment availability, and performance. Natural conditions and other factors affect project progress and can also be the cause of delays in project completion, resulting in the planned time to exceed the previous specified time. With the implementation of the Fast Track method on Bore Pile's work, it can be seen how quickly it will take for the work to be continued and the development project of the Regional Hospital to be completed. This research will focus on the analysis of time and cost acceleration in order to determine the comparison of time obtained with the scheduling start time and also on the analysis of cost outcomes required for acceleration, It is also a matter of consideration for contractors and for project owners and can also be a medium of learning especially in construction management. From the analysis of this study, the result was that the time obtained from the acceleration of activities was 20 days from the initial duration of 110 days to 90 days with the required cost of Rp 9,466,975,861.54, and the cost difference between normal cost and Fast Track method was Rp 238,218,404,57.